Evidence of a large “prehistorical” earthquake during Inca times? New insights from an indigenous chronicle (Cusco, Peru) - Combey A. (2020)
A colonial chronicle written by the indigenous Peruvian author Pachacuti Yamqui Salcamaygua ([1613?]) relates a legend of the sudden appearance of a huge animal – kilometres in length and approximately 4 m in width – and described as the Andean snake-like deity amaru. Pachacuti Yamqui alleged that this fantastic event occurred on the day that the sovereign Pachacuti Inca Yupanqui's eldest son was born around 1440 CE, and was named “Amaru”. We suggest that the underlying event was an earthquake, and that the propagation of the surface rupture across the landscape resembled a sudden appearance of a snake-like being wriggling over the mountains and leaving an undulating surface trace. The concordance between the snake's route and the layout of a major fault complex above Cusco, as well as several ethnographic testimonies, support this hypothesis. Although little is known about pre-1532 CE seismicity, the current tectonic settings of the Cusco area point to seismic awareness of the Incas (ca. 1300–1532 CE). Independent results from architectural and paleoseismological fields in the Cusco area corroborate a significant impact of large earthquakes on local societies. In Peru, without pre-Hispanic written sources, the oral folklore and traditions preserved in Spanish chronicles offer a relevant, but still underexploited resource for identifying paleo-extreme events. Combining multidisciplinary geomorphic observations, archaeological evidence and historical sources, we revisit this legendary episode and its possible implications. © 2020 Elsevier Ltd